Edukasi Keselamatan Radiasi Saat Pemeriksaan X-Ray bagi Siswa SMA untuk Meningkatkan Pengetahuan dan Mengurangi Ketakutan Berlebih - Niwele Amelia (Universitas Pahlawan Tuanku Tambusai, 2026)
Radiation safety constitutes a fundamental aspect of radiology services. Nevertheless, prevalent misconceptions often lead to excessive fear (radiophobia) regarding medical radiation, particularly among students, due to a lack of accurate information. This community engagement program aimed to enhance high school students' understanding of X-ray safety, the ALARA principle, and ambient radiation doses in daily life. The methodology employed included interactive education, visual demonstrations, discussions, and the distribution of educational leaflets. Involving 85 student participants, the program evaluation revealed a significant improvement in knowledge, with the average pretest score of 52.3 increasing to 86.7 in the posttest. Furthermore, 91% of participants reported diminished anxiety towards medical radiation following the intervention. This program demonstrated effectiveness in elevating radiation safety literacy among students and offers a viable model for sustainable health education in schools.